IMPLICATION OF PESTICIDES USAGE ON FRESHWATER FISH: A REVIEW (FUDMA JOURNAL OF SCIENCES, 2021)
Pesticides play  a significant role in improving food production through control against harmful pests with low labour and efforts while on the other hand are regarded as aquatic pollutants. These toxicants persist in aquatic environment and cause harmful effects to non- target organisms including fish.   The development of pesticide tolerant species led to the need and use of varieties of pesticides with the risk of exposure to many compartments including water. Many pesticides have been proscribed for agricultural purposes by the regulatory agencies such as WHO (2020). However, It is unfortunate that many of these are sold in Nigeria or donated by donor agencies.  The donated pesticides often become â€œobsoleteâ€ while in stock due to poor logistics and delays in receiving them at the point of need. The review on the classification, bioavailability, biotransformation, the direct and indirect effects of pesticides on freshwater fish was carried out. Biomarkers of pesticides toxicity that induce alterations in fish physiology were discussed; these include: behavioral changes such as erratic swimming, hyperactivity among other alterations. Other alterations include feeding behaviour, fluctuation in antioxidant enzyme activities, histology, haematology, growth performance and DNA damage.
Keywords: Bioavailability, Biotransformation, Pesticides Harmful Effect, Freshwater fish, Physiology